Annie John - Kincaid, Jamaica (New York : Farrar, Straus, Giroux, 1997)
A fictional account of a young girl's coming of age in Antigua, from a doted upon childhood to an adolescence fraught with events and alliances leading her away from mutual complacent acceptance.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Mothers and daughters -- Antiqua -- Fiction; Teenage girls -- Antigua -- Fiction; Bildungsromans; Girls -- Fiction; Mother-daughter relationship -- Fiction; Teenagers -- Fiction; Antigua -- Fiction; Bildungsromane; Domestic fiction